SCHOOL COMMITTEE PERFORMANCE IN MINIMUM SERVICE STANDARD OF BASIC EDUCATION - Akhirin Akhirin (At-Tarbiyat, 2020)
This research is aimed at describing the implementation of Minimum Standard of Education (MSE) and performance of school committee in supervising the implementation of Minimum Standard of Education (MSE) at Junior High School in Jepara. This research is descriptive research with qualitative approach. The data collection was conducted through questionnaire, interview, documentation study, and observation. The data analysis used descriptive qualitative. The research result showed that the implementation of Minimum Standard of Education (MSE) had average good score at State of Junior High School and less than good in Private Junior High School. In the meantime, the supervisory duties of school committee to the implementation of MSE showed poor grades.